Library Electronic services in Ahmed Al-Farsi Library: a simulated approach - Dsilva, Suchita Noel; Waydande, Prof (Dr) Hindurao (IJRDO- Journal of Educational Research, 2017)
Academic libraries have important factors in the process of learning among other factors of education and research. Due to the new electronics technology development and new electronics storage media for storage and dissemination of information, Libraries are reengineering its services; we speak about electronic references, full text data access, Web resources, that are integral part of education in the electronic environment. E-services can be used byboth consumers and businesses, and can be accessed via a wide range of information appliances (Hoffman, 2003, p.53). This paper focuses on the challenges that e-services are posing and will pose for research purpose. The study has focused on the issues thatUniversity of Bahrain (UOB), College of Health Science (CHS) library has had to deal with as a result of e-services adoption as well as the future challenges that e-services provide for CHS, Ahmed Al-Farsi Library (AAFL). The study is based on a number of conversations with UOB library management & staff and information provided on the Web page. The librarians also have to adapt to this new development for e-delivery and storage and dissemination of information, to form and to inform about the e-resources for learning. We have to develop added value services to the role of library as a key factor in learning.